Map of Fair location (J.C. Bardell)
Treasure Island on San Francisco Bay, site of the 1939 Golden Gate International Exposition and thereafter an airport, is being linked to the San Francisco-Oakland Bay Bridge by a $600,000 system of modern highways across Yerba Buena Island, where the $77,000,000 bridge becomes a tunnel. Six lanes wide at its narrowest point, this highway system will carry eleven different lanes of traffic on an intricate grade-separation that will eliminate left-turns. The 12,000-car parking lot on Treasure Island will be ten minutes from central San Francisco or Oakland ferries will aid in carrying 20,000,000 visitors to the $50,000,000 World's Fair at the peak rate of 50,000 an hour.